Hubungan Manajemen Konflik dengan Kepuasan Kerja Tenaga Pendidik dan Kependidikan - Khoerunnisa, Siti Noorbaeti; Heri Khoiruddin; Kasmin (Education Management: Jurnal Manajemen Pendidikan Islam, 2024)
This research aims to describe conflict management and job satisfaction and analyze the relationship between conflict management and job satisfaction of teaching and education staff in State Madrasah Aliyah throughout Bandung City. The approach used is quantitative with descriptive correlational analysis methods. The data in this study was obtained through the results of distributing a questionnaire using a Likert scale model consisting of four alternative answer choices given to 40 respondents. Based on the results of conflict management research, it is included in the medium category, namely 3.37 from the results of data processing. The job satisfaction of teaching and education staff is categorized as moderate, namely 3.27 from the results of data processing. Based on the results of the correlation calculation between variable So it can be concluded that there is a relationship between employee job satisfaction management in State Madrasah Aliyah throughout Bandung City. The results of the correlation test calculation show that the significance of conflict management of madrasa heads with teacher performance is 0.001 < 0.05. The results of the correlation test are positive, which means that if conflict management is further improved, employee job satisfaction will also increase. Then, from the results of the coefficient of determination test, it was obtained (R square) of 0.385, which means that the conflict management variable with employee job satisfaction has a contribution of 38.5%.